Manual for pre-clinical removable prosthodontics - Bazirgan, Muhamad Husain Kassim; Mustafa, Ammar A.; Hashim, Md. Arshad (IIUM Press, 2011)

(untitled)
DENTURE PROSTHODONTICS ‘Complete denture prosthodontics’ is defined as that body of knowledge and skills pertaining to the restoration of the edentulous arch with a removable dental prosthesis. While ‘complete denture prosthetics’ is defined as: 1. the replacement of the natural teeth in the arch and their associated parts by artificial substitutes 2. the art and science of the restoration of an edentulous mouth The complete denture treatment is the restoration of a completely edentulous (no teeth) by an artificial substitute called “Complete denture” which is the replacement of the upper (maxillary) and lower (mandibular) lost teeth by an appliance that may replace the lost teeth and their associated adjacent structure. The complete denture treatment is a treatment that deals with a pathological case, of having no teeth that renders the patient lacking the function of cutting the food as well as being psychologically disturbed of having the cosmetic corruption of the appearance of the face by losing the muscular support of the facial expression. The complete denture could be considered unique when compared to other prostheses replacements in the body, since it deals with both function and appearance, or in other words it deals with the physiology and psychology. Replacing missing teeth is a technical as well as a clinical procedure, a denture cannot be thought of like any other part of the body that can be worn or fitted according to size as no denture of one patient can fit another patient’s mouth even if they were twins. 7 The clinical part of the treatment is to obtain the informative anatomical landmarks from the patient oral cavity by the dentist, and transfer it to the laboratory where the technical part is taken over by the technician. The clinical and the technical aspects of the complete denture fabrication have got an ample intermingling relation that makes the dentist as well as the technician, scientifically and technically attentive of the work of the other. The complete procedure of making a denture should be made clear to the dental student prior to the clinic attendance, thus preparing the student to be fully aware of both the technical (preclinical) as well as the clinical aspects of the treatment and by mastering both it will be possible to understand the sequential steps and their consequences.